Молекулярно-генетичні і імуногістохімічні параметри прогресування поліпів та раку товстої кишки - Шишкін, Максим Андрійович; Шишкин, М. А.; Shyshkin, M. A. (Запорізький державний медичний університет, 2021)
Визначено, що провідну роль в прогресуванні аденом ДТК відіграє дисплазія з підвищенням рівня проліферації та апоптозу епітелію, а також експресії EpCAM та кількості ALDH1+ клітин. Провідну роль в прогресуванні зубчастих утворень ДТК відіграє дисплазія з підвищенням рівня проліферації та апоптозу епітелію, в гіперпластичних поліпах – і збільшення кількості мікросудин. High-grade поліпи ДТК відрізняються від G1 КРА достовірно нижчими показниками експресії р53, VEGF-A, СD44, ALDH1, зубчасті утворення – і нижчим рівнем експресії Ki-67. При прогресуванні КРА від I до IV стадії зростає експресія мРНК KRAS, TP53 і експресія р53, знижується експресія мРНК Ki-67 і експресія Ki-67. Також знижуються експресія мРНК CDH1 і експресія Е-кадгерину, лишаються підвищеними експресія мРНК CTNNB1 і експресія β-катеніну. Одночасно знижується експресія CK-20, зростає експресія віментину і α-SMA. Метастатична КРА відрізняється від неметастатичної достовірно вищими показниками експресії мРНК KRAS, мРНК TP53 і р53, VEGF-A, VEGFR-2, віментину, α-SMA, MUC1, EpCAM, CD44, ALDH1 клітинами строми; достовірно нижчими показниками експресії мРНК гену Ki-67 і Ki-67, Е-кадгерину, CK-20, MUC2, MUC4. Установлено, что ведущую роль в прогрессировании аденом ДТК играет дисплазия с повышением уровня пролиферации и апоптоза эпителия, а также экспрессии EpCAM и количества ALDH1+ клеток. Ведущую роль в прогрессировании зубчатых образований ДТК играет дисплазия с повышением уровня пролиферации и апоптоза эпителия, в гиперпластических полипах – и рост числа микрососудов. High-grade полипы ДТК отличаются от G1 КРА достоверно более низкими показателями экспрессии р53, VEGF-A, СD44, ALDH1, зубчатые образования – и более низким уровнем экспрессии Ki-67. При прогрессировании КРА от I до IV стадии возрастает экспрессия мРНК KRAS, TP53 и экспрессия р53, снижается экспрессия мРНК Ki-67 и экспрессия Ki-67. Также снижаются экспрессия мРНК CDH1 и экспрессия Е-кадгерина, остаются повышенными экспрессия мРНК CTNNB1 и экспрессия β-катенина. Одновременно снижается экспрессия CK-20, возрастает экспрессия виментина и α-SMA. Метастатическая КРА отличается от неметастатической достоверно более высокими показателями экспрессии мРНК KRAS, мРНК TP53 и р53, VEGF-A, VEGFR-2, виментина, α-SMA, MUC1, EpCAM, CD44, ALDH1 клетками стромы; достоверно более низкими показателями экспрессии мРНК Ki-67 и Ki-67, Е-кадгерина, CK-20, MUC2, MUC4. In the thesis, it was established that epithelial dysplasia with increased proliferation and apoptosis levels, as well as increased EpCAM expression and increased number of ALDH1+ epitheliocytes and stromal cells play a key role in the progression of conventional adenomas of the distal colon. Epithelial dysplasia with increased proliferation and apoptosis levels plays a key role in the progression of serrated lesions of the distal colon, augmented by the increased number of microvessels in hyperplastic polyps exclusively. It was shown that high-grade conventional adenomas of the distal colon differ from G1 colorectal adenocarcinoma by significantly lower р53, VEGF-A, СD44 expression indexes, as well as significantly lower ALDH1 expression by stromal cells; serrated lesions differ by significantly lower Ki-67, p53, VEGF-A, VEGFR-2 expression indexes, as well as significantly lower СD44 and ALDH1 expression by stromal cells. During the colorectal adenocarcinoma progression from the Ist up to the IVth stage, transcriptional activities of KRAS and TP53 genes increase, whereas transcriptional activity of Ki-67 gene decreases, immunohistochemical р53 and Ki-67 expression indexes change accordingly. During the progression, transcriptional activity of CDH1 and E-cadherin expression level decrease, while transcriptional activity of CTNNB1 and β-catenin expression level keep elevated. At the same time, indicators of epithelialmesenchymal transformation appear: CK-20 expression level decreases, vimentin and α-SMA expression levels increase. During the colorectal adenocarcinoma progression from the Ist up to the IInd stage, MUC1, VEGF-A, VEGFR-2, CD44 expression levels increase, as well as ALDH1 expression by stromal cells, whereas MUC2 and MUC4 expression levels decrease. The colorectal adenocarcinoma progression from the IInd up to the IIIrd stage differs by the elevation of Cdx-2 and EPCAM expression levels, while the progression from the IIIrd up to the IVth stage differs by the elevation of EPCAM expression level and ALDH1 expression level by both cancer сells and stromal cells. Metastatic colorectal adenocarcinoma differs from non-metastatic one by significantly higher mRNA KRAS, mRNA TP53 and р53, VEGF-A and VEGFR-2, vimentin, α-SMA, MUC1, EpCAM, CD44 expression levels, as well as higher ALDH1 expression by stromal cells; and by significantly lower mRNA Ki-67 and Ki-67, Е-cadherin and CK-20, MUC2 and MUC4 expression levels.
Молекулярно-генетические и иммуногистохимические параметры прогрессирования полипов и рака толстой кишки
Molecular-genetic and immunohistochemical parameters of colonic polyps and colonic cancer progression
Keywords: колоректальні поліпи; колоректальний рак; проліферація; апоптоз; K-RAS; ангіогенез; стовбурові клітини; CD44; ALDH1; EpCAM; CDH1; Е-кадгерин; CTNNB1; β-катенін; епітеліально-мезенхімальний перехід; колоректальные полипы; колоректальный рак; пролиферация; ангиогенез; стволовые клетки; β-катенин; эпителиально-мезенхимальный переход; colorectal polyps; colorectal cancer; proliferation; apoptosis; VEGF-A; VEGFR-1; VEGFR-2; CD34; angiogenesis; stem cells; E-cadherin; β-catenin; CK-20; α-SMA; vimentin; epithelial-mesenchymal transition; mucins; Cdx-2